Are benefits of others important? The interaction effect of moral identity and construal level on green consumption. Issue 1 (3rd September 2018) - Wu, Bo; Li, Dongjin; Zhang, Chubing
Abstract : Purpose: The purpose of this paper is to examine the interaction effect of moral identity and construal level on consumer green consumption and the mediating role of pro-environmental self-accountability. Design/methodology/approach: The authors examined the hypotheses in two experiment studies. In study 1, the authors measured participants' chronic individual difference of moral identity and primed construal level. In study 2, the authors primed moral identity and measured chronic individual difference of construal level. The authors also measured pro-environmental self-accountability in these two studies. Findings: The results reveal that construal level moderates the relationship between moral identity and consumer green consumption, specifically, when consumers are induced a high construal level, moral identity has no effect on consumer green consumption, while when consumers are induced a low construal level, moral identity has a positive effect on consumer green consumption; the interaction of moral identity and construal level on green consumption is mediated by pro-environmental self-accountability. Research limitations/implications: This research enriches the literature on how to improve consumer green consumption, and thus has some managerial and public policy implications. But the authors only chose students as participants and the dependent measures are also limited. Future research can choose other type of sample and other dependent measures to test the generalization of the conclusion. Originality/value: Prior literature of green consumption lacks research on mediation mechanism. Due to prior literature gaps, the authors integrate social-cognitive perspective moral identity theory, especially the in-group circle expansion of moral identity, and construal level theory to investigate the moderating effect of construal level on the relationship between moral identity and green consumption and the mediation effect of pro-environmental self-accountability.